1991
DOI: 10.1007/bf00928683
|View full text |Cite
|
Sign up to set email alerts
|

Echinostoma caproni in rats: worm population dynamics and host blood eosinophilia during primary infections with 6, 25 and 50 metacercariae and resistance to secondary and superimposed infections

Abstract: Hooded-Lister rats were inoculated with 6, 25, 50 or 100 metacercariae of the intestinal trematode Echinostoma caproni. Worm establishment and the pattern of egg excretion were followed during the course of primary infections with 6, 25 and 50 metacercariae. Peripheral blood eosinophilia was followed at all infection levels. After 1 month, worm recovery and faecal egg output showed a gradual decline with increasing duration of infection. High worm burdens were expelled later than smaller worm burdens, and egg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…Golden hamsters only develop a limited capacity to expel primary infections resulting in chronic infections. In contrast, E. caproni in rats undergoes a gradual worm rejection, and the infection is lost at 49-70 DPI (Hansen et al, 1991;Toledo, Espert, Muñoz-Antoli et al, 2003). Our study compares the course of the infection in both host species by presenting quantitative data on the kinetics of antibodies and coproantigens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Golden hamsters only develop a limited capacity to expel primary infections resulting in chronic infections. In contrast, E. caproni in rats undergoes a gradual worm rejection, and the infection is lost at 49-70 DPI (Hansen et al, 1991;Toledo, Espert, Muñoz-Antoli et al, 2003). Our study compares the course of the infection in both host species by presenting quantitative data on the kinetics of antibodies and coproantigens.…”
Section: Discussionmentioning
confidence: 99%
“…According to these works, hamsters display a high degree of compatibility, whereas rats exhibit a low level of compatibility (Christensen et al, , 1990Odaibo et al, 1988Odaibo et al, , 1989Hansen et al, 1991;Mahler et al, 1995) using the criterion of worm survival. Golden hamsters only develop a limited capacity to expel primary infections resulting in chronic infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in the number of blood eosinophils have been observed in rats infected with E. caproni (Hansen et al 1991) , and mice (BALB/c and C3H/HeN strains) infected with E. hortense ) . The degree of blood eosinophilia was closely related with the worm burden in each case.…”
Section: Eosinophilsmentioning
confidence: 95%
“…For each echinostome species, expulsion of primary infections occurs rapidly in a number of rodent species, while in other species chronic infections are developed . The elimination of E. caproni primary infections in rats occurred at 7-8 weeks postinfection (wpi) (Hansen et al 1991 ;Toledo et al 2004a) , whereas worm survival in hamsters showed a persistence of at least 20 wpi (Toledo et al 2004b) , and in mice the longevity of the adult worms reached 23 wpi (Fried and Peoples 2007) . The elimination of E. trivolvis from mice occurs within 2-3 wpi (Weinstein and Fried 1991) , while in hamsters worms survived for up to 123 days postinfection (dpi) (Mabus et al 1988) .…”
Section: Manifestations Of Resistance To Infectionmentioning
confidence: 99%